(untitled) (Damascus University Journal for engineering sciences, 2021)
Portland cement is a hydraulic binder which bonds aggregates together in the concrete mixture. Production of Portland cement starts with two basic materials: a calcareous material and argillaceous material, contain four main oxides: CaO, SiO2, Al2O3, Fe2O3. These raw materials interact in the kiln forming complex chemical compounds such as: Tricalcium silicate C3S, Dicalcium silicate C2S, Tricalcium aluminate C3A, Tetracalcium alminoferrite C4AF. These compound especially C3S, C2S, when hydrated, provide the desired mechanical properties of cement such as compressive strength at different ages. The effects of the ratios of these oxides forming Portland cement, its fineness and the role of lime saturation factor on its mechanical properties especially compressive strength were investigated in this research. A research programme was applied to four samples of Syrian cement (CEM I 32.5N). The samples were taken virtually from privet sector and from state sector of cement factories. The chemical analysis of cement samples was obtained using XRD (X-ray diffraction) method. Their fineness was measured and compared with to Syrian specification 1673/1997. The results showed that only one sample has a chemical composition and compressive strength at age of 28 days that compatible with Syrian specification 1887/1997 and European standard requirements EN 197-1/2011. The values of cement fineness were acceptable for all samples and played an important role in rapid development of strength at early age (7 days). The importance in this research is to highlight the quality of cement industry in the present time, and is to investigate if it is compliance with the Syrian and European standards especially a significant increase in cement demand is expected when starting the reconstruction period.